The Assessment of Competiencies for Ambulance Personnel –Problems and Challenges - Dambe, Gundega; Atstāja, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of this paper is to clarify whetherperformances assessment at a work place promotes Ambulance professionals for personnel development, and if it providesthe possibility to assess personnel’s competence and professionalism. The results of State Emergency Medical Service ambulance personnel’s performance assessment in years 2013 and 2014 are analysed in the research. The results obtainedthat using existing methods for performance assessment, there are not possibility to assess personnel’s competence and professionalism for building personnel development programs in the future.